Basketball training frequency is associated with executive functions in boys aged 6 to 8 years - Xu, Yue; Zhang, Wanxia; Zhang, Kexin; Feng, Min; Duan, Tianqi; Chen, Yilin; Wei, Xuexiang; Luo, Yanlin; Ni, Guoxin (Frontiers in Human Neuroscience, 2022)
This study investigates the relationship between the frequency of basketball training and executive functions (inhibitory control, working memory, and cognitive flexibility) in boys aged 6 to 8. A total of 40 boys recruited from a local after-school basketball training club were divided into a low-frequency group (once a week) and a high-frequency group (at least twice a week). An additional 20 age-matched boys recruited from a local elementary school were considered as the control group (no training experience). All subjects conducted the Stop-signal task, the N-back task, and the switching task at rest. The mean reaction time and accuracy data obtained from each task were used in statistical analysis. There was no significant group difference in either the accuracy or reaction time of inhibitory control. Meanwhile, no significant difference was found in the reaction time of working memory across groups. However, the high-frequency group exhibited significantly higher accuracy (93.00±4.31%) with regard to working memory than the low frequency group (85.4±6.04%, P<0.001) and the control group (83.73±7.70%, P<0.001), respectively. A positive correlation was also found between the accuracy of working memory and groups. Furthermore, in comparison with the control group, the high frequency group exhibited significantly higher cognitive flexibility accuracy (91.93±7.40 % vs. 85.70±9.75%, P=0.004) and shorter reaction time (934.24±213.02ms vs. 1122.06±299.14ms, P <0.001). There was also a positive correlation between the accuracy of cognitive flexibility and groups. These findings suggest that regular basketball training, especially with higher frequency, is beneficial to working memory and cognitive flexibility in boys aged 6 to 8.